Training on Making Healthy and Nutritious Snack Products: KEPAYA (Papaya Chips) in Bati-Bati District, Tanah Laut Regency - Dyah Sri Wulandari; Ray Melvin Resubun; Irma Suryani; Mahmudah; Teresia Miranti (Community Development Journal, 2023)
Papaya fruit is a fruit that has a high nutritional content, especially levels of vitamin C and vitamin A. Every 100 grams of papaya contains 3.65 mg of vitamin A and 78 mg of vitamin C. The whole papaya plant is very beneficial for human health. Other benefits, can be used as an alternative medicine for diseases, constipation, heart disease, cancer, high cholesterol, acne, and inflammation. Tanah Laut Regency is the largest papaya producing area in South Kalimantan, as a papaya producing area, of course the people have the potential to develop various business opportunities. The problem encountered in the community is a lack of knowledge about the other benefits of papaya fruit. chips snacks, most of the people's income is only from agriculture, from the existing problems, the team provides a solution, namely to provide knowledge about other benefits of papaya fruit, provide training on making papaya chips, and utilize the potential of papaya fruit as an effort to increase the income of the community in Bati District -Bati, with partners PKK RT 08 Liang Anggang Village through this Community Service will add references for the community to be able to do entrepreneurship from the papaya fruit they produce, a product that has a sale value, is healthy and nutritious such as making papaya fruit into chips snacks which can be enjoyed by all groups, with these various benefits, this Community Service is carried out in order to utilize the potential of natural resources in the Tanah Laut Regency area, especially the Bati-Bati District, where most of the people work as farmers. The community knows other benefits of papaya fruit which can be used as a product or other way of consuming papaya fruit, creating KEPAYA snack products, Papaya Chips which are nutritious and healthy. The results achieved from the output of this program are that it can produce a processed snack derived from papaya fruit where this papaya fruit has many benefits for our bodies and to increase the income of the people in the Bati-Bati District.